Effectiveness of a Process to Create a Strategy Route Map for Pushing Health Policies into Local Health Insurance Funds - Siriwanarangsun, Somjit; Saengngern, Sane (Journal of Health Science of Thailand, 2017)
The objective of this study was to assess the effectiveness of a strategy route map (SRM) to push health policies into local health insurance funds (LHIFs) in Sukhothai Province. The study was conducted during October 2555 to March 2556 involving 14 LHIFs randomly selected to participate by dividing into an experimental group (7 LHIFs) and a control groups (the other 7 LHIFs). Intervention for the experimental group included a workshop on a strategy route map. A set of questionnaires was used to collect data on (1) the outcome on the integration of provincial health policies into the LHIFs, (2) awareness of LHIF members on public health policy, and (3) community satisfaction and participation of 4 population groups including mothers and children, old age and disability group, occupational group and people with chronic diseases. Data were analyzed by using percentage, mean, standard deviation and independent samples t-test. It was found that the experimental group had integrated significantly higher number of health policies into the LHIFs. The levels of awareness, satisfaction and participation among the experimental group at the end of the study were significantly higher than those before the study (p<0.05). Such significant increase was not observed in the control group. The study results indicated that a process to establish SRM should be promoted in order to push provincial health policies into the LHIFs.